Studying the Factors Affecting Osteoporosis in Women with The Logistic Regression Analysis - Kılıç, B., Taşkıran, Y., Yücel, A. S., Korkmaz, M. (My University, 2014)
The purpose of this investigation is to study the factors affecting osteoporosis in women with the logistic regression analysis in order to evaluate the effect of those risk factors. The age of women ranged between 40-70 years. A questionnaire was prepared for this study and the questions were directed to patients. The research was conducted on a total of 250 patients. As the dependent variable is in a categorical data type with two levels, binary logistic regression analysis was applied. According to the analysis results, such factors as age, weight, calcium amount of the individual, duration of the exercise, genetic factors, being in menopause and smoking have significant effect pushing individuals towards being osteoporotic. In order to prevent osteoporosis, a person should lose weight, increase weekly exercises, be careful about the calcium amount in her body and reduce smoking. particularly elder ones.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Osteoporosis Risk Factors Menopause Smoking Weight